2004
DOI: 10.1038/sj.ejhg.5201235
|View full text |Cite
|
Sign up to set email alerts
|

Paraoxonase 1 polymorphisms and survival

Abstract: The antioxidant enzyme paraoxonase 1 (PON1) has previously been suggested to confer protection against coronary heart disease (CHD), one of the main causes of death in the Western world. Two coding polymorphisms, 55M/L and 192Q/R, and a promoter variant, À107C/T, has been extensively studied with respect to susceptibility to CHD. In this study, we have investigated the impact of these three polymorphisms on mortality using a sample of 1932 Danish individuals aged 47-93 years, previously used in gene-longevity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
25
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 18 publications
2
25
1
Order By: Relevance
“…However, these findings were not always consistent. 22,23 In our study, we did not replicate any of the reported associations, but instead identified association at rs854563 (P CMH ¼1.92Â10 À04 ), which lies within the same LD block as the L55M variant. rs854563 showed stronger association than the L55M variant itself or the haplotype tagged by both SNPs.…”
Section: Discussioncontrasting
confidence: 89%
“…However, these findings were not always consistent. 22,23 In our study, we did not replicate any of the reported associations, but instead identified association at rs854563 (P CMH ¼1.92Â10 À04 ), which lies within the same LD block as the L55M variant. rs854563 showed stronger association than the L55M variant itself or the haplotype tagged by both SNPs.…”
Section: Discussioncontrasting
confidence: 89%
“…We present our results on genotype-based analysis in Table 2, where, as described in methods, risk and frequency parameters are estimated for each genotype against the reference. Although only a subsample was used, our model detected PON1 192 Q/Q and Q/R genotypes as of potential influence (P ¼ 0.062 for Q/R and P ¼ 0.076 for Q/Q genotypes), a result consistent with that of Christiansen et al (2004). In Figure 2, we show the observed and the estimated genotype frequency patterns for all genotypes at the three loci.…”
Section: Example Applicationsupporting
confidence: 65%
“…Recent association studies are increasingly emphasizing the important roles that genes may play in affecting human survival at advanced ages (Bonafe et al 2002;Christiansen et al 2004;Bellizzi et al 2005;Hurme et al 2005). Further studies using efficient analytical tools are needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations